An Integrated Sharia-Based Performance Management Framework for Indonesian SMEs - Ida Nuraida (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study develops a structured Sharia-based approach to employee performance management in Indonesian small and medium-sized enterprises (SMEs). SME performance systems often emphasize efficiency, while Islamic ethical and spiritual principles remain under operationalized within formal HR mechanisms. The study integrates Maqāṣid al-Sharī‘ah and Islamic Work Ethics into a three-dimensional performance framework encompassing spiritual motivation, ethical conduct, and organizational contribution, addressing the limited operationalization of Islamic ethics in SME performance research. A qualitative exploratory conceptual design is employed through document analysis of classical Islamic texts and contemporary management literature. Four foundational principles: intention (niyyah), trustworthiness (amanah), excellence (ihsan), and justice (‘adl), are translated into a three-dimensional Sharia-based performance framework encompassing spiritual motivation, ethical conduct, and organizational contribution. The framework advances Islamic management and IHRM scholarship by repositioning Sharia principles as an operational evaluative infrastructure that bridges spiritual accountability and formal HR systems, while offering practical guidance for ethically resilient SMEs in Indonesia.